Analysis of the Application of Accounting to Micro, Small and Medium Enterprises (MSMEs) in Kecamatan Bulango Utara - Mattoasi Mattoasi; Victorson Taruh; Novrianti Supu (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
MSMEs have been chosen by most Indonesians to get out of social problems. Such a large contribution MSMEs make to economic development. Seeing such a large contribution made by MSMEs, more attention is needed to develop and maintain the existence of MSMEs, because in fact MSMEs have weaknesses that usually occur in financial management. Many businesses are experiencing financial problems, as a result of which the business has gone out of business. Financial management problems are factors that can cause failure in MSMEs. One way of settlement is with correct accounting practices. Of course, this applies to all MSMEs of all types, including MSMEs in North Bulango District. The purpose of this study is to find out the extent of the application of accounting carried out by MSMEs in North Bulango District, to know the perception of MSMEs in North Bulango District towards accounting, and the factors that cause low accounting for MSMEs in North Bulango District. The research was conducted using a descriptive quantitative approach. The data source used is primary data. Data collection techniques are carried out by observation, interviews, documentation, and data triangulation. The results showed that Small, Micro, and Medium Enterprises (MSMEs) in North Bulango District have not implemented accounting records properly based on SAK EMKM so that they do not display information about the rate of return on capital, assets, debt and capital in more detail. The results of another study found that the obstacles faced by MSME companies in implementing SAK EMKM were lack of knowledge about accounting in accordance with SAK EMKM and lack of awareness of business actors in the importance of implementing accounting in accordance with SAK EMKM.